A social work perspective on developing a contextualized model of Aggression Replacement Training (ART) within an Arab setting. Issue 2 (2nd April 2020) - Almakhamreh, Sahar Sulieman; Asfour, Hana Zuhair; McFarlane, Mary Anne; Woods, Joe; Lankshear, Ian; Bogschütz, Zoltán
ABSTRACT: A new approach to adolescent aggression was adopted as a pilot project by the Social Work Department at Al Balq'a Applied University in Jordan. This came in response to the need to find alternative solutions to student expulsion at the University, as well as the push by the Ministry of Justice to support community sentences for offenders. An adapted version of the Aggression Replacement Training (J-ART) program was used that was sensitive to the sociocultural context understudy. This study assessed the effectiveness of the J-ART program outcomes in promoting the wellbeing of student offenders. The conceptual framework is framed around a social work perspective with focus on strength-based and human rights approaches. A total of 44 participants took part in four focus groups. Findings highlighted reduced levels of aggression and positive learning experiences among participants. This pilot study produced evidence to support institutional reform in Jordan's juridical system.